Detailed Mapping of Determinants within the Porcine Endogenous Retrovirus Envelope Surface Unit Identifies Critical Residues for Human Cell Infection within the Proline-Rich Region - Argaw, Takele (American Society for Microbiology, 2012)
Replication-competent porcine endogenous retroviruses (PERVs) are either human cell tropic (PERV-A and PERV-B) or non-human cell tropic (PERV-C). We previously demonstrated that PERV in vitro cell tropism is modulated by 2 residues within the C terminus of SU and that the PERV receptor binding domain (RBD) extends beyond the variable regions A and B (VRA and VRB, respectively), to include the proline rich-region (PRR) of SU (M. Gemeniano et al., Virology 346:108–117, 2000; T. Argaw et al., J. Virol. 82:7483–7489, 2008). The present study aimed to identify the specific elements within the PERV RBD that interact with the C-terminal elements of SU to facilitate human cell infection. We constructed a series of chimeric and mutated envelopes between PERV-A and PERV-C and using pseudotyped retroviral vectors to map the human cell tropism-determining sequences within the PERV RBD. We show that the PRR from PERV-A is both necessary and sufficient to allow human cell infection when substituted into the homologous region of the PERV-C envelope carrying two C-terminal amino acid substitutions shown to influence human cell tropism, Q374R and I412V (PERV-Crv). Furthermore, substitution of a single amino acid residue in the PRR of the non-human-tropic PERV-Crv envelope allows vectors carrying this envelope to infect human cells. Receptor interference assays showed that these modified PERV-C envelopes do not bind either of the human PERV-A receptors, suggesting the presence of a distinct human PERV-C receptor. Finally, vectors carrying these modified PERV-C envelopes infect primary human endothelial cells, a cell type likely to be exposed to PERV in clinical use of certain porcine xenotransplantation products.